القوة الناعمة الصينية في عصر المعرفة (الموارد والتحديات) - أبوحلاوة, كريم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث لإلقاء الضوء على مفهوم القوة الناعمة ومواردها التي يزيد حُسن استخدامها من قوة الدولة وقدرتها على تحقيق أهدافها السياسية والاقتصادية؛ وبالتالي زيادة أهميتها على الصعيد الدولي والإقليمي. واليوم في عصر المعرفة والتكنولوجيا، وما تمنحه العولمة من حرية حركتهما أصبح من السهل على الحكومات التوجه نحو الشعوب والتعريف بحضارتها وثقافتها وإمكاناتها وانجازاتها. فقد قدم هذا البحث صورة عن موارد القوة الناعمة الصينية وكيف تمكنت الصين من استخدامها للوصول إلى أهدافها الاقتصادية والسياسية، وإقامة علاقات جيدة مع الشعوب قبل دولها وكان لها ذلك بشكل خاص في القارة الإفريقية من خلال تقديمها للمساعدات الصحية للمتضررين من الحروب والفقراء، كما شكلت المساعدات التنموية دوراً هاماً في نمو القوة الناعمة الصينية بشكل عام وفي أفريقيا بشكل خاص. وأشار البحث إلى دور معاهد كونفوشيوس في توسيع وإغناء ثقافة الشعوب عن الصين وتشجيعهم لزيارة الصين، وإقامة أعمال تجارية هناك. إلا أن هذا التقدم الذي حصدته الصين جراء تنمية مواردها الناعمة، قد واجه تحديات تتعلق بمورد (السياسات الحكومية) التي فشلت الصين بتنميته وجعلها عاجزة أو ضعيفة للولوج في عقول الشعوب الأوربية والدول المتقدمة بشكل عام. وخلص البحث إلى أهمية تعزيز السياسات الحكومية في الصين؛ حيث شكل هذا تحدياً أمامها للوصول إلى عقول شعوب العالم الأوروبي وليس فقط دول العالم الثالث، وزيادة أهمية الاعلام الجديد (شبكات التواصل الاجتماعي( في التعريف بثقافة الصين وحضارتها. This research aims to light on the concept of soft power and its resources, which are served the state to enhance the power of the state and its ability to achieve its political and economic objectives; thus increasing its importance at the international and regional levels. Nowadays, in the age of knowledge and technology, where the globalization gives them free movement. All that grant the governments the chance for contact with peoples around the world to introduce their civilization, culture, potential and achievements.This research has presented a picture of China's soft power resources and how China able to use them to reach its economic and political goals and establish good relations with the peoples before their countries. This has been particularly in the African continent by providing health assistance to those affected by war and the poor. Has played an important role in the growth of Chinese soft power in general and in China in particular. The research pointed to the role of Confucius Institutes in expanding the culture of people from China and encouraging them to visit China and establish business there. However, China's progress in developing its soft resources, it has challenged by the resource (government policies) that China has failed to develop and to reach for European’s people and other in developed nations. The research concluded that it is important to strengthen China's government policies. This has challenged it to reach the minds of the peoples of the European world, and to increase the importance of the new media in introducing China's culture and culture.